Erratum from the Editor - Stulz, René M. (Journal of Finance, 1999)
To avoid a Y2K problem, we upgraded the software that tracks the work of referees early this year. Unfortunately, as a result of this switch in software, our list of referees in the annual report is incomplete. I apologize to the following individuals who refereed for the Journal in 1998 but were omitted from the list of referees in the annual report: Adler, Michael Ait-Sahalia, Yacine Barclay, Michael Berger, Allen Bergman, Yaacov Bessembinder, Hendrik Biais, Bruno Black, Harold Bloomfield, Robert Bradley, Michael Chan, Kalok Chen, Nai-fu Cooper, Ian Coval, Joshua Crack, Timothy Cuny, Charles Dammon, Robert Easton, peter Fleming, Jeff George, Thomas Gorton, Gary Hadlock, Charles Helwege, Jean Heston, Steven Hirshleifer, David Holden, Craig Huang, Ming Hughes, Patricia Humphrey, David Jagannathan, Ravi Karolyi, Andrew Kimball, Miles Kothari, S.P. Lee Inmoo Liu, Hong Livingston, Miles Maksimovic, Vojislav Malatesta, Paul Mark, Nelson Mester, Loretta Metrick, Andrew Mulherin, J. Nimalendran, M. Perrakis, Stylianos Pinegar, J. Pulvino, Todd Rosen, Richard Schnitzlein, Charles Scruggs, John Serrat, Angel Shanken, Jay Shin, Han Shroff, Pervin Stambaugh, Robert Tehranian, Hassan Vu, Joseph Walkling, Ralph Weinstein, Mark West, Kenneth Wood, Robert Zapatero, Fernando Zhou, Chunsheng Zhou, Zhongquan Zingales, Luigi